Heuristic Evaluation of UI/UX to Enhance Experience and Sales in E-commerce - Rendi Andika; Dram Renaldi (bit-Tech, 2024)
User experience and interface (UI/UX) are critical elements in e-commerce websites, where an unattractive design and lack of user engagement can negatively impact potential sales. This study was conducted to evaluate the effectiveness of the UI/UX on a company's e-commerce website, which has received complaints from users regarding the interface design and low purchase interest. The evaluation was conducted using the Heuristic Evaluation method, applying Nielsen's 10 principles with three evaluators to identify interface issues affecting user experience. The results of the study revealed significant weaknesses in three main principles: "Visibility of System Status," "Match Between System and the Real World," and "Help and Documentation." Each of these principles received a score of category 2 on the Likert Scale, indicating substantial usability weaknesses in the UI. Solutions implemented included improving icon visibility, providing clearer system feedback, using more understandable language, and adding comprehensive online guidance. After these improvements, a re-evaluation showed score increases: "Visibility of System Status" improved from 38.4% to 49.6%, "Match Between System and the Real World" from 38.4% to 51.2%, and "Help and Documentation" from 37.6% to 48.8%. These findings indicate that UI/UX improvements based on Heuristic Evaluation can enhance the overall user experience, which is expected to help the company attract potential buyers and increase sales potential through the e-commerce website.